Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Section 10.4 - Adding, Subtracting, and Multiplying Radical Expressions - Exercise Set: 50

Answer

$(3x-\sqrt{2})(3x-\sqrt{2})=9x^{2}-6x\sqrt{2}+2$

Work Step by Step

$(3x-\sqrt{2})(3x-\sqrt{2})$ Rewrite this expression as $(3x-\sqrt{2})^{2}$: $(3x-\sqrt{2})(3x-\sqrt{2})=(3x-\sqrt{2})^{2}=...$ Use the formula for squaring a binomial to evaluate this power. The formula is $(a-b)^{2}=a^{2}-2ab+b^{2}$. For this particular case, $a=3x$ and $b=\sqrt{2}$ Substitute the known values into the formula and simplify if possible: $...=(3x)^{2}-2(3x)(\sqrt{2})+(\sqrt{2})^{2}=9x^{2}-6x\sqrt{2}+2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.